2019
DOI: 10.1101/734764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cancer causes metabolic perturbations associated with reduced insulin-stimulated glucose uptake in peripheral tissues and impaired muscle microvascular perfusion

Abstract: 20Background: Redirecting glucose from skeletal muscle and adipose tissue, likely benefits the 21 tumor's energy demand to support tumor growth, as cancer patients with type 2 diabetes have 30% 22 increased mortality rates. The aim of this study was to elucidate tissue-specific contributions and 23 molecular mechanisms underlying cancer-induced metabolic perturbations. 24Methods: Glucose uptake in skeletal muscle and white adipose tissue (WAT), as well as hepatic 25 glucose production, were determined in contr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Yet only a fraction of active Akt is required to fully activate GLUT4 translocation in muscle cells (Fazakerley et al, 2019;Wang et al, 1999), suggesting that the small reductions in proximal insulin signaling observed in T2D may not suffice to cause insulin resistance. Furthermore, skeletal muscle insulin resistance can occur with seemingly normal (Høeg et al, 2011;Kim et al, 1999;Ramos et al, 2020;Raun et al, 2018) or even elevated proximal insulin signaling (Han et al, 2020), clearly demonstrating that there is no uniform association between proximal insulin signaling and glucose uptake. Instead, or in addition, the distal parts of the insulin signaling cascade must be considered.…”
Section: Insulin Signaling Defectsmentioning
confidence: 99%
“…Yet only a fraction of active Akt is required to fully activate GLUT4 translocation in muscle cells (Fazakerley et al, 2019;Wang et al, 1999), suggesting that the small reductions in proximal insulin signaling observed in T2D may not suffice to cause insulin resistance. Furthermore, skeletal muscle insulin resistance can occur with seemingly normal (Høeg et al, 2011;Kim et al, 1999;Ramos et al, 2020;Raun et al, 2018) or even elevated proximal insulin signaling (Han et al, 2020), clearly demonstrating that there is no uniform association between proximal insulin signaling and glucose uptake. Instead, or in addition, the distal parts of the insulin signaling cascade must be considered.…”
Section: Insulin Signaling Defectsmentioning
confidence: 99%
“…Most preclinical models adding a physical activity or exercise treatment before either the rapid tumor growth stage or cachexia onset can attenuate or prevent wasting (Gould et al, 2013; Hardee et al, 2019). Furthermore, impaired systemic metabolism (Das et al, 2011; Han et al, 2020; Kir et al, 2014) and muscle metabolic dysfunction (Brown et al, 2017; Han et al, 2020) have been reported before cachexia onset and are potential drivers of accelerated protein turnover during cachexia's progression(VanderVeen et al, 2017). However, the effect of exercise on the feeding and fasting metabolic regulation during cachexia initiation is uncertain.…”
Section: Introductionmentioning
confidence: 99%